Hepatoprotective agents in the management of intrahepatic cholestasis of pregnancy: current knowledge and prospects - Shan, Dan; Dai, Siyu; Chen, Qian; Xie, Yupei; Hu, Yayi (Frontiers in Pharmacology, 2023)
Intrahepatic cholestasis of pregnancy (ICP) is characterized by unexplained distressing pruritus in the mother and poses significant risk to the fetus of perinatal mortality. Occurring in the second and third trimester, the serum bile acid and aminotransferase are usually elevated in ICP patients. Ursodeoxycholic acid (UDCA) is the first line drug for ICP but the effectiveness for hepatoprotection is to a certain extent. In ICP patients with severe liver damage, combination use of hepatoprotective agents with UDCA is not uncommon. Herein, we reviewed the current clinical evidence on application of hepatoprotective agents in ICP patients. The underlying physiological mechanisms and their therapeutic effect in clinical practice are summarized. The basic pharmacologic functions of these hepatoprotective medications include detoxification, anti-inflammation, antioxidation and hepatocyte membrane protection. These hepatoprotective agents have versatile therapeutic effects including anti-inflammation, antioxidative stress, elimination of free radicals, anti-steatohepatitis, anti-fibrosis and anti-cirrhosis. They are widely used in hepatitis, non-alcoholic fatty liver disease, drug induced liver injury and cholestasis. Evidence from limited clinical data in ICP patients demonstrate reliable effectiveness and safety of these medications. Currently there is still no consensus on the application of hepatoprotective agents in ICP pregnancies. Dynamic monitoring of liver biochemical parameters and fetal condition is still the key recommendation in the management of ICP pregnancies.